Occult large epiphyseal solitary plasmacytoma at multidetector rowcomputer tomography detected by magnetic resonance imaging - De Filippo, M.; Pogliacomi, F.; Albisinni, et al., U. (Acta Biomedica Atenei Parmensis, 2008)
Myeloma or Kahler-Bozzolo disease represents around 1% of all malignant tumors and 10% of the haematological variety; it is a B-lymphocellular malignant neoplasia which originates from plasma cells that produce monoclonal immunoglobulin, infiltrating in and destroying the adjacent bone tissue. Myeloma may be distinguished at radiological imaging in four distinct types: single osseous lesions (solitary plasmacytoma), diffused skeletal effects (myelomatosis), diffused osteopenia and sclerosing myeloma. It is known that initial osteolysis may not be shown through radiographic examination or CT; the lysis only becomes evident when there is a bone loss of over 50%, usually in the presence of a =/> 0,5 cm focal lesion. We present here the clinical-radiological aspects of a solitary bone plasmacitoma (SBP) of the knee of a 35 year old male which was not evidenced at radiological examination or CT but was evident as a 3 cm focal alteration at MR. The lesion was confirmed by PET and the histological diagnosis was performed by a CT guided bioptic sample.